Integrating network analysis and experimental validation to reveal the mechanism of Cuscuta chinensis lam. Extract in the treatment of IgA nephropathy - Xianlong Zhang; Mingjie Liang; Ziyang Lin; Minyi Li; Tingting Duan; Yun Han; Lanqing Meng; Mengqiu Li; Guixuan Lin; Tao Xia; Ying Lai; Boen Liang; et al. (Journal of Functional Foods)
Purpose/aim: IgA nephropathy represents a prevalent form of the common kidney disease globally, accounting for the majority of cases of chronic kidney disease and renal failure. Cuscuta chinensis Lam has been shown to nourish the liver and tonify the kidney, consolidate essence, and arrest polyuria, However, whether Cuscuta chinensis Lam has the protective effects on IgA nephropathy and the underlying mechanisms remain unclear. Methods: A network pharmacology analysis was employed to examine the interactions between the active ingredients and core targets, with a view to elucidating the possible potential mechanisms in Cuscuta chinensis Lam. extract (CCLE) in the treatment of IgA nephropathy. Sprague-Dawley rats were administered with bovine serum albumin (BSA) with a dose of 800 mg/kg−1 every other day for a period of 12 weeks to obtain IgA nephropathy model. lipopolysaccharide (LPS) was injected through the tail vein at a dose of 0.05 mg at the 6th week, 8th week, and 10th week; 0.1 mL of CCl4 and 0.3 mL of castor oil were injected subcutaneously once a week for 12 weeks; the rats were gavaged with CCLE for 6 weeks from 13th week. Biochemical analysis, tGFR analysis, enzyme-linked immunosorbent assay (ELISA) analysis, periodic acid-Schiff (PAS) staining, Masson staining, and immunofluorescence staining were employed to evaluate the impact of CCLE on IgA nephropathy in rat. Western blotting was utilized to investigate the underlying mechanisms. Results: The results demonstrated that a significant decrease in the glomerular filtration rate, accompanied by a notable elevation in biochemical indexes in rats in model group, including the ratio of total protein to creatinine in urine, sCr, BUN, TG, AST, ALT, IL-1β and TNF-α; additionally, the rats in the model group exhibited substantial histopathological alterations, characterized by the presence of many IgA deposits; CCLE has been demonstrated to enhance the glomerular filtration rate, downregulate the levels of sCr, BUN, TG, AST, ALT, IL-1β and TNF-α, reduce the IgA deposition, and ameliorate the histopathological changes in IgA nephropathy rats; Western blotting demonstrated CCLE can suppress the expressions of p-PI3K, p-AKT, p-IKK, p-NF-κB, and p-IκB in IgA nephropathy rats. Conclusion: CCLE demonstrated superior protective effects on BSA + LPS + CCl4 + castor oil-induced IgA nephropathy in rats by regulating the PI3K-AKT and NF-κB signaling pathways. These findings suggest that CCLE has potential as a therapeutic agent for the treatment of IgA nephropathy.